Analysis of the Impact of Implied Scenarios on the Reliability of Computational Concurrent Systems - Roriz, Alexandre Vaz; Rodrigues, Genaína Nunes; Laranjeira, Luiz A. (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2014: Anais do VIII Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software, 2014)
Current approaches to model-driven software development have led to the use of scenarios to perform analysis of non-functional requirements of a software system in its early stages of development. The presence of implied scenarios is a phenomenon that can be observed in concurrent systems modeled in the form of Message Sequence Charts. This paper presents a methodology for the identification and evaluation of the qualitative and quantitative impact of the referred scenarios on the reliability of such systems. To the best of our knowledge, there is no previous research contribution in the literature in this regard. The applicability, as well as feasibility, of this methodology is illustrated on the example of a boiler control system. The results are then used to support the architectural refinement of the system ensuring the elimination of the undesirable implied scenarios identified and the consequent improvement in the software system reliability. The usefulness of the proposed methodology is thus confirmed to facilitate the construction of reliable concurrent software systems since the early stages of the development cycle.